MON-062 46 XX DSD Due to POR Deficiency - Reddy, Nithin Modhugu (J Endocr Soc, 2020)
Background PORD (P450 oxidoreductase deficiency) is a rare form of CAH with marked phenotypic variations due to differences in the degree of steroid hormone excess/deficiency. PORD results in17αhydroxylase/17,20lyase- CYP17, 21αhydroxylase- CYP21, and aromatase- CYP19A1 inhibition. In the absence of characteristic skeletal features of Antley Bixler phenotype, differentiating PORD from other types of CAH is challenging. Case details 04 day child, second of the non-identical twins, product of 2(nd) degree consanguinity, third in birth order was brought with abnormal genitalia. The other male twin had no genital ambiguity but had pigmented scrotum. There was no adrenal crisis in index case or maternal virilization. First child is normal female. Child was hemodynamically stable weighed 02 kgs and measured 51 cms, had no hyperpigmentation, skeletal deformities or dysmorphic features. Phallus was 10mm, clitoral index 40mm(2) with single urogenital opening and posteriorly fused labia (anogenital ratio 0.6).Gonads were not palpable. Karyotype was 46XX with normal Mullerian structures and non-visualized gonads on ultrasonography. Biochemical workup showed random plasma glucose level of 99mg/dl and normal electrolytes. Baseline serum 8am Cortisol was 1.15 mcg/dl (normal 5-18 mcg/dl) and 17OHP was 20 ng/ml (normal < 02 ng/ml). Serum Androstenedione level was 0.39 nmol/L (normal 0.5-3.4 nmol/L). In view of clinical, laboratory and imaging findings, presumptive diagnosis of 46 XX DSD due to 21 alpha hydroxylase deficiency CAH was made. Oral Hydrocortisone 15mg/m(2) and Fludrocortisone 0.05 mg were initiated. Therapy was monitored with serum 17(OH)P levels and Androstenedione. Genetic testing for 21 alpha hydroxylase gene however came negative. This led to further genetic mutational analysis, and there was a homozygous R457H POR gene mutation at exon 12 leading to protein change p.Arg457His (nucleotide change c.1370G>A), confirming PORD. Retrospectively, maternal triple test done during the candidate pregnancy showed low serum estriol, suggestive of placental aromatase deficiency. Mineralocorticoid supplements were stopped thereafter. Conclusions PORD needs to be considered and differentiated from garden variety of CAH in 46 XX DSD when elevation of 17(OH)P is modest with isolated cortisol deficiency and aromatase deficiency (evidenced by low maternal estriol levels and/or virilization), as its course and follow up are different.